(untitled) (Revista científica Olimpia, 2019)
The study "Strategic diagnosis of the conditions for the development of physical activity in the student population of the career of Medical Emergencies and Disasters of the University Specialized of the Americas (UDELAS) of Panama ", revealed the insufficiencies that existed in the curriculum of that career, also showing the poor participation of students in extracurricular physical activities, which had an insufficient physical preparation to undertake, upon graduation of the university, the professional work of his profile with the required competences. To contribute to improve physical preparation, the development of basic motor skills, and utilitarian motor skills according to the competencies required by the profile of the professional who graduated from that career, a curricular strategy of physical activities was developed, derived from the results of the diagnosis integral made, and taking into account the contents that appear in the curricular mesh, the analysis of the normative documents of the university, and the opinion of teachers and directors of the same. The strategy was evaluated through the criterion of specialists to determine its theoretical feasibility, those who generally thought it was very appropriate, and allowed to conclude that it was feasible to be applied in the career of Medical Emergencies and Disasters of the Specialized University of the Americas.